2019
DOI: 10.1111/imm.13140
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V expression on CD4+ T cells with regulatory function

Abstract: SummaryRegulatory T (Treg) cells induce immunologic tolerance by suppressing effector functions of conventional lymphocytes in the periphery. On the other hand, immune silencing is mediated by recognition of phosphatidylserine (PS) on apoptotic cells by phagocytes. Here we describe expression of the PS‐binding protein Annexin V (ANXA5) in CD4+ CD25hi Treg cells at the mRNA and protein levels. CD4+ ANXA5+ T cells constitute about 0·1%–0·6% of peripheral blood CD3+ T cells, exhibit co‐expression of several Treg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Additionally, annexin B11 ( AnxB11 ) was also upregulated in the bacteriomes of both species. Mammalian annexins are inhibitors of immune responses, where they suppress inflammatory responses during apoptosis [ 99 , 100 ]. This observation further supports a more tolerant microenvironment in both tsetse species G. brevipalpis and G. morsitans likely aimed to sustain high bacterial densities within bacteriomes when compared to midguts.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, annexin B11 ( AnxB11 ) was also upregulated in the bacteriomes of both species. Mammalian annexins are inhibitors of immune responses, where they suppress inflammatory responses during apoptosis [ 99 , 100 ]. This observation further supports a more tolerant microenvironment in both tsetse species G. brevipalpis and G. morsitans likely aimed to sustain high bacterial densities within bacteriomes when compared to midguts.…”
Section: Resultsmentioning
confidence: 99%
“…When studied by GSEA, CD4 + T cells from AML patients were enriched of signatures related to regulatory T (Treg) cells (Figure 5E). Of note, some ADM coexpressed genes, including JUNB, CDKN1A, ANXA5, CYBB, NFKBIZ, that were upregulated in CD4 + T cells from AML patients compared with cells from healthy controls (Figure 5B), are known to participate to the Treg phenotype (65)(66)(67)(68)(69).…”
Section: The Adm Gene Network Is Enriched Of Inflammatory Signatures In Leukemic Cells and Of Immunomodulatory Genes In T Cells From Aml mentioning
confidence: 99%
“…Studies by Fischer et al(15) observed that Ag stimulation of CD4 1 T cells led to the transient externalization of PS and that treatment with Annexin V diminished proinflammatory cytokine secretion. Moreover, Bollinger et al(46)…”
mentioning
confidence: 99%